My Bright Midnight : A Novel - Russell, Josh (Book collections on Project MUSE., 2010)
Walter Schmidt's life isn't simple: His wife Nadine wants to live next door to her dead first husband's mother, the Mississippi River is three blocks down the street and rising dangerously, FDR is dead, and the war seems like it will never end--but for the most part, things are going Walter's way. Then one bright April morning in 1945, Walter comes home early from work to find Nadine in bed with his best friend, Sammy. Shocked into silence, when she then calls him a "kraut," Walter becomes even more confused. True, he's a German immigrant, but he's lived in New Orleans for almost tw